Yasmin la jardinera ebook - Aly, Hatem (Yasmin, 2020)
¡Es primavera! Yasmin y su papá trabajan con entusiasmo en el jardín. Yasmin se encarga de cuidar unas plantitas con flores. Las pone al sol, las riega y les pone tierra fértil... entonces, ¿por qué se marchitan? Un día, Yasmin observa a Nani sentada al sol y descubre la solución perfecta para sus plantas. It's spring! Yasmin and her baba are excited to plant their garden, and Yasmin chooses a flower seedling. She gives it plenty of sun, water, and good soil . . . so why is it wilting? Watching Nani sit in the sun gives Yasmin a bright idea and she knows just what her little plant needs.